The Influence of the External Environment on Organizational Performance: A Literature Review from the Perspective of Strategic Management - M. Ayyanhar Arifin Djafar; M. Rivai Faruk; Rabiah Al Adawiyyah; Alhusain Bin Syeh Abubakar (Amkop Management Accounting Review (AMAR), 2026)
This study aims to analyze the influence of the external environment on organizational performance from the perspective of strategic management through a literature review approach. The external environment refers to factors beyond an organization’s control that nevertheless have a significant impact on the achievement of organizational goals. This study employs a descriptive qualitative method using content analysis of various relevant scholarly literature sources. The findings indicate that external environmental factors, such as economic conditions, political dynamics, social changes, technological development, and the level of industry competition, influence organizational performance both directly and indirectly. Furthermore, strategic management serves as an adaptive mechanism that enables organizations to identify opportunities and threats and formulate appropriate strategies in response to external environmental dynamics. These findings affirm that an organization’s ability to understand and respond to changes in the external environment is a key factor in improving performance and sustaining competitive advantage.